A novel hamstring strain injury prevention system: post-match strength testing for secondary prevention in football - Wollin, M.; Thorborg, K.; Drew, M.; Pizzari, T. (British Journal of Sports Medicine, 2020)
In this letter, we report our proof of concept hamstring injury prevention system that incorporated secondary prevention for hamstring injury in football. We also compared the occurrence and burden of hamstring injury in a cohort where secondary prevention was implemented in addition to standard practice (primary and tertiary prevention).